2018
DOI: 10.1111/jpn.12895
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of Artemisia argyi polysaccharide on peripheral blood leucocyte of broiler chickens

Abstract: This study was conducted to investigate the immunomodulatory effect of a water-soluble polysaccharide extracted from Artemisia argyi (AAP) in vitro. The effect was assessed in peripheral blood leucocytes (PBLs) of broilers, which were incubated with different AAP concentrations (0, 25, 50, 100, and 200 μg/ml) for 24 hr at 37°C in a 5% CO incubator. The results showed that, compared with the control group, immunoglobulin M (IgM) concentration was increased in the supernatant of the 100 μg/ml AAP-treated group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…The extraction method of crude polysaccharide from F. velutipes was in compliance with our previous literature (Zhang, Shi, et al, ). Crude polysaccharides (100 mg) was weighted and dissolved in 10 ml of distilled water.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…The extraction method of crude polysaccharide from F. velutipes was in compliance with our previous literature (Zhang, Shi, et al, ). Crude polysaccharides (100 mg) was weighted and dissolved in 10 ml of distilled water.…”
Section: Methodsmentioning
confidence: 81%
“…The extraction method of crude polysaccharide from F. velutipes was in compliance with our previous literature (Zhang, Shi, et al, 2018).…”
Section: Extraction and Purification Of Polysaccharidesmentioning
confidence: 99%
“…Among the bio‐active components, methoxyflavones which belong to flavonoids have been reported to be involved in preventing against oxidative damage and inflammation (Li, Lo, & Ho, ; Wang et al, ). Furthermore, total polysaccharides were recently extracted from A. argyi and their immunomodulatory activity was confirmed (Zhang et al, ). Previous study reported that the antioxidant protection of apple, similar to that of many other dietary plants, may be due largely to the presence of phenolics (Eberhardt, Lee, & Liu, ; Tsao, Yang, JCY, & Zhu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Artemisia species are one of the most popular plants in Chinese traditional herbal medicine and are frequently used for the treatment of diseases such as malaria, hepatitis, cancer, inflammation and infections caused by fungi, bacteria and viruses (Wright, ). Owing to their rich nutrients and bio‐active components, the genus Artemisia plants and their extracts can be used as natural Chinese herbal medicine feed additive, which plays important roles in promoting animal growth performance, improving the quality of animal products and enhancing the immune function and antioxidant activity (Bhakuni, Jain, Sharma, & Kumar, ; Brisibe, Umoren, Owai, & Brisibe, ; Gouveia & Castilho, ; Kim, Adesogan, & Shin, ; Kim et al, ; Li et al, ; Sani, Mohammadi, Sendi, Abolghasemi, & Mehr, ; zhang et al, , ). Among genus Artemisia plants, Artemisia ordosica , a perennial herb, is one of the main shrubs growing in north and northwest areas in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation